2014
DOI: 10.1371/journal.pone.0090140
|View full text |Cite
|
Sign up to set email alerts
|

Can a Resident's Publication Record Predict Fellowship Publications?

Abstract: BackgroundInternal medicine fellowship programs have an incentive to select fellows who will ultimately publish. Whether an applicant's publication record predicts long term publishing remains unknown.MethodsUsing records of fellowship bound internal medicine residents, we analyzed whether publications at time of fellowship application predict publications more than 3 years (2 years into fellowship) and up to 7 years after fellowship match. We calculate the sensitivity, specificity, positive and negative predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…3,4 Still, whether higher scholarly activity in applications reflects any higher likelihood to pursue an academic career is unclear. 5 The increasing prevalence of non-PhD graduate degrees may reflect either greater enrollment in combined degree programs such as an MD/MPH or MD/MBA program, or advanced training before medical school.…”
Section: Trends In the Dermatology Residency Match From 2007 To 2018: Implications For The Dermatology Workforcementioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Still, whether higher scholarly activity in applications reflects any higher likelihood to pursue an academic career is unclear. 5 The increasing prevalence of non-PhD graduate degrees may reflect either greater enrollment in combined degree programs such as an MD/MPH or MD/MBA program, or advanced training before medical school.…”
Section: Trends In the Dermatology Residency Match From 2007 To 2018: Implications For The Dermatology Workforcementioning
confidence: 99%
“…2 AMs are more common on certain weight-bearing areas of the feet in Japanese and white patients 3,4 ; acral melanocytic nevi (AMN) are more common on noneweight-bearing areas in Korean patients. 5 If AMs evolve from AMN or an intermediate precursor, the location and incidence of AMs and AMN or atypical AMN should correlate. Herein, we compare the distribution of AMN and atypical AMN to the distribution of AM on the plantar surface of the foot in a predominately white population.…”
Section: Density and Distribution Of Acral Melanocytic Nevi And Acral Melanomas On The Plantar Surface Of The Footmentioning
confidence: 99%
“…The most common type of publications were observational studies (1015/2538, 40.0%), and the most common journal published in was The Laryngoscope (n = 378; impact factor = 2.34 in 2018; Table 2). Graduates had a mean H-index of 3.7 (SD 3.7) and the highest H-index was 25.…”
Section: Resultsmentioning
confidence: 99%
“…Although several reports show promising results, investigations of publication trends among internal medicine and neurosurgery residency graduates have yielded conflicting findings. [22][23][24][25] Within the field of otolaryngology specifically, Kohlert et al 26 found that publishing at least 1 paper during medical school made an individual almost 6 times more likely to publish in residency. Furthermore, Eloy et al 27 found a considerable difference in h-indices among faculty members of academic otolaryngology departments with higher publication output than those without.…”
Section: Introductionmentioning
confidence: 99%
“…The ACGME requires residents to participate in the production of scholarly endeavours; our experience is that such success is extremely valuable, especially as a platform to learn how to initiate scientifically excellent productivity during fellowships training (ACGME.org, 2018). One study, however, demonstrated a poor correlation between the number of publications that a trainee spawns during residency and fellowship (Prasad et al, 2014). The ACGME places greater value on the acquisition of tools learned during residency rather than on the number of scholarly products at that training level (Philibert et al, 2013).…”
Section: Resultsmentioning
confidence: 99%